Interconnection of 802.11b Wireless Physiologic Monitors with a 802.11a/B/G Wireless Voip Network at Santa Cabrini Hospital’s Emergency Care Unit - Zoabli, Gnahou; Knights, James; Giguère, Denis; Thomason, Ken (CMBES Proceedings, 2008)
Santa Cabrini Hospital (SCH) initiated the integration of VoIP wireless communication and patient monitoring systems in their Emergency rooms (ER). The new Bell-Nortel wireless network uses an IEEE 802.11a/b/g protocol while the GE mobile DASH 3000 monitoring system of the ER was initially an IEEE 802.11 one upgraded to IEEE 802.11b. A joint study conducted with the engineering teams of Bell, Nortel and GE Healthcare demonstrated the feasibility of this multivendor hardware (Symbol vs Nortel) and software (GE vs Bell) integration. During the first four months following the integration, issues regarding the secure cohabitation of both systems and electromagnetic interferences (EMI) with the medical equipment used in the ER were assessed. The functionality and clinical benefits of this integration have been demonstrated and the installation of wireless IP telephones in the other critical care departments of the hospital is being scheduled. Keywords: Wireless monitoring system, Wireless VoIP, Emergency room, EMI